Effect of Renal Sympathetic Denervation on Specific MicroRNAs as an Indicator of Reverse Remodeling Processes in Hypertensive Heart Disease. Issue 6 (24th February 2016) - Dörr, Oliver; Liebetrau, Christoph; Möllmann, Helge; Gaede, Luise; Troidl, Christian; Lankes, Simone; Guckel, Denise; Boeder, Niklas; Voss, Sandra; Bauer, Timm; Hamm, Christian; Nef, Holger
Abstract : A total of 90 consecutive patients undergoing renal sympathetic denervation (RSD) were included in this study. A significant reduction in office systolic blood pressure (SBP) of 21.1 mm Hg ( P <.001) was documented 6 months after RSD. At this time point, circulating concentrations of microRNA (miR)‐133a were significantly increased (sevenfold; P <.001) compared with baseline values. Correlation analysis showed a significant relationship between baseline SBP values and SBP reduction ( P <.001) as well as between miR‐133a baseline levels and the increase in miR‐133a expression ( P <.001) after the 6‐month follow‐up. The effect of RSD on miR‐133a expression was significantly greater in patients at high risk for hypertensive heart disease. In addition to the effective blood pressure reduction in response to RSD, this study demonstrates an effect of RSD on miR reflecting cardiovascular reverse remodeling processes. Thus, these results provide information on a beneficial effect of RSD on cardiac recovery in patients at high risk for hypertensive heart disease.